Electronic Banking 2001
DOI: 10.1007/978-3-322-86627-1_15
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Banking in Malaysia: A Note on Evolution of Services and Consumer Reactions

Abstract: Developments in information technology and telecommunications have set in motion an electronic revolution in the Malaysian banking sector. This in turn has resulted in new delivery channels for banking products and services such as the automated teller machines (ATM's), telebanking and PC-banking. In this context, the purpose of this study is to examine the evolution of electronic banking in Malaysia, analyze the various electronic delivery channels utilized by local banks and to assess the consumers' reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
24
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 1 publication
1
24
0
Order By: Relevance
“…This implies that users are still doubtful of the confidentiality and safety of the technology. The support for hypothesis 3 reflects similar arguments in previous studies (Suganthy, 2001;O'Connel, 1997;Cooper, 1997;Ramsay and Smith, 1999;Guru et al, 2000) who found that security have greater impact on the adoption intent of Internet banking. This factor is a potential impediment to consumers transacting through Internet.…”
Section: Hypothesis 2: Ease Of Use Positively Affects the Intention Tsupporting
confidence: 88%
See 1 more Smart Citation
“…This implies that users are still doubtful of the confidentiality and safety of the technology. The support for hypothesis 3 reflects similar arguments in previous studies (Suganthy, 2001;O'Connel, 1997;Cooper, 1997;Ramsay and Smith, 1999;Guru et al, 2000) who found that security have greater impact on the adoption intent of Internet banking. This factor is a potential impediment to consumers transacting through Internet.…”
Section: Hypothesis 2: Ease Of Use Positively Affects the Intention Tsupporting
confidence: 88%
“…Sathye (1999) emphasized that customers, particularly the senior citizens, prefer personal interaction and that they have technology phobia. In Malaysia also at the same, bank customers till patronize bank branches and they remain to value personal interactions (Guru et al, 2000).…”
Section: Costmentioning
confidence: 99%
“…In the context of factors within the control of management, the immediate factors that would have an impact on bank profitability would be those factors that affect a bank's net interest income (Guru et al, 2000). To this extent, the net interest margin could be expected to have a positive influence on the bank's profitability.…”
Section: Hypothesesmentioning
confidence: 99%
“…E-banking or Internet banking in a retail banking segment has offer consumers a more control on managing their account activities [2]. They can access their account detail from their computer via Internet connection to the bank's server.…”
Section: Motivationmentioning
confidence: 99%